Analysis of Ambiguity in Humor: A Pragmatic Analysis of Wordplay in YouTube Channel “We Got The Chocolates” - Moh. Kifly S. Rasyid; Hanisah Hanafi; Fahria Malabar (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study is grounded in the linguistic phenomenon of phonetic ambiguity as a strategy to create verbal humor in digital spoken discourse. The objective is to analyze how segmental sound structures are realised in phonetic wordplay and elucidate how these structures trigger dual meaning interpretations through a pragmatic framework. A descriptive qualitative research design was employed, using spoken dialogues from the "We Got The Chocolates" YouTube channel as the primary data source. Data were collected through systematic observation and transcription of five purposively selected videos, then analysed using a co-textual pragmatic approach in conjunction with International Phonetic Alphabet (IPA) transcriptions and Grice's Cooperative Principle. The findings reveal two primary operational patterns: Perfect Puns (13 instances) relying on absolute homophony, and Imperfect Puns (17 instances) relying on phonetic similitude. These phonetic manipulations consistently trigger humor through a calculated strategy of multiple maxim flouting, where the flouting of the Maxim of Manner via acoustic camouflage is systematically paired with the flouting of the Maxim of Quality or the Maxim of Relation. The study concludes that spoken humor operates as a cognitive resolution process where structural acoustic illusion and narrative incongruity mutually reinforce each other. However, limitations include the restriction to segmental sound manipulation (excluding suprasegmental features) and the reliance on interpretative qualitative pragmatic methodology.